Metode Personal Extreme Programming pada Pengembangan Sistem Rekam Medis Elektronik Klinik Gigi - Yusuf, Dianni; Panduardi, Farizqi; Arrizki, Mohammad Rashel; Kristanto, Sepyan Purnama; Utomo, Agus Priyo (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2025)
Resource limitations, costs, time estimates and changing requirements are some of the importat factors that must be considered in the small-sclae software development stage. This research aims to develop a web-based Medical Records System (MRS) to accelerate the registration and storage of patient medical records. The software development method used is Personal Extreme Programming (PXP), which assists individual developers in building systems that are responsive to changing user needs. The PXP stages include requirements and planning, iteration initialization, design, implementation, system testing, and a retrospective. The requirement planning stage is represented by 8 user stories. There are 4 iterations in the development process with an estimated development time of 38 days. The system was designed using wireframe, implemented using the Laravel framework, and tested using Unit Testing and User Acceptance Testing (UAT). Test results showed that the system was well received by 10 users, with average UAT scores of Very Good for patients, doctors and clinic administrator. The system development time was 8 days faster because the PXP method minimized system development documentation. So, it can be concluded that the PXP method can be a solution for individual developers in developing small-scale clinical systems.